Southern Association of Colleges and Schools Accreditation:Impact on Elementary Student Performance - Bruner, Darlene Y.; Brantley, Lance Lamar (Education Policy Analysis Archives, 2004)
Currently, 848 Georgia public elementary schools that house third- and fifth-grades in the same building use the Southern Association of Colleges and Schools (SACS) accreditation as a school improvement model. The purpose of this investigation was to determine whether elementary schools that are SACS accredited increased their levels of academic achievement at a higher rate over a five-year period than elementary schools that were not SACS accredited as measured by the Iowa Test of Basic Skills (ITBS). Independent variables included accreditation status, socioeconomic status (SES) of schools, and baseline scores of academic achievement. Dependent variables included mathematics and reading achievement scores. There was a statistically significant difference found when examining the SES of schools and baseline scores of the elementary schools. SACS accredited elementary schools had higher SES and higher baseline scores in third- and fifth grade mathematics and reading. However, the multiple regression model indicated no statistically significant differences in gain scores between SACS accredited and non-SACS accredited elementary schools in third- and fifth-grade mathematics and reading achievement during the five year period examined in this study.